The application of yaw sensor for measuring carriage system - Chinchusak, Wanchai; Tipsuwanporn, Vittaya; Numsomran, Arjin; Krongratana, Viriya (My University, 2016)
Laser interferometers have generally been used for the angular measurement of measuring tape calibration systems. Yaw error measurements using a yaw sensor have been carried out to determine the characteristics of yaw errors and analyze the behaviors of the structural guide. The yaw sensor technique is identical to the error compensation used in a measuring tape calibration, and also has some special parameters. However, the yaw error observation period is very short, but it is sufficiently accurate for a carriage yaw sensor. This paper presents the yaw sensor innovation for the measuring carriage application that would be compensated by using yaw error is approximately minimized to 65 arcsec and its repeatability is less than 30arcsec.
Keywords: yaw measurement; yaw sensor